Status and challenges of multi-junction solar cell technology - Baiju, Adil; Yarema, Maksym (Frontiers in Energy Research, 2022)
The ongoing energy transition to curb carbon dioxide emissions and meet the increasing energy demands have enhanced the need for integration of renewable energy into the existing electricity system. Solar energy has been gaining an increasing market share over the past decade. Multi-junction solar cells (MJSCs) enable the efficient conversion of sunlight to energy without being bound by the 33% limit as in the commercialized single junction silicon solar cells. III-V semiconductors have been used effectively in space applications and concentrated photovoltaics (CPV) over the past few decades. This review discusses the working and components of MJSCs at cell level as well as module level for space applications and CPV. The fabrication procedure, material acquirement of MJSCs is analyzed before introducing the current challenges preventing MJSCs from achieving widespread commercialization and the research direction in the future where these challenges can be addressed.